(untitled) (Nepalese Medical Journal, 2021)
Introduction: The outbreak of coronavirus diseases 2019 (Covid-19) caused by SARS-COV-2 which started in Wuhan china led to an alarming level of spread and severity. In Nepal, the first case of COVID-19 was reported on 23.1.2020 and has become a global health crisis since then. The clinical presentation and outcome of patients with COVID-19 have been variable in different countries and therefore it is important to analyze as well as document the clinical behaviors of this disease in the local population so we have reported the clinic-epidemiological profile, outcome, and its association with conjunctivitis during the second wave of this pandemic which hit Nepal badly hoping this study will be helpful to tackle the future surges of COVID-19 as well. Materials and Methods: This was a prospective, single-center study where the data regarding epidemiology, demography, common clinical presentation as well as management and outcome of COVID-19 Patients were retracted and analyzed. Results: A total of 238 COVID-Positive patients were admitted out of which 60% were male and 39.9% people belonged to Dang valley itself with dyspnea (67.2%) was the commonest symptoms followed by fever in 59.7% of patients. Out of these patients 9 patients presented with ocular symptom conjunctivitis. Conclusions: Mild conjunctivitis manifesting as conjunctival congestion is common and one of the major ocular manifestations in COVID -19 positive patients.